Abiotic formation of methyl iodide on synthetic birnessite: A mechanistic study - Allard, Sebastien; Gallard, H. (Elsevier, 2013)
Methyl iodide is a well-known volatile halogenated organic compound that contributes to the iodine content in the troposphere, potentially resulting in damage to the ozone layer. Most methyl iodide sources derive from biological activity in oceans and soils with very few abiotic mechanisms proposed in the literature. In this study we report that synthetic manganese oxide (birnessite δ-MnO2) can catalyze the formation of methyl iodide in the presence of natural organic matter (NOM) and iodide. Methyl iodide formation was only observed at acidic pH (4–5) where iodide is oxidized to iodine and NOM is adsorbed on δ-MnO2. The effect of δ-MnO2, iodide and NOM concentrations, nature of NOM and ionic strength was investigated. High concentrations of methyl iodide were formed in experiments conducted with the model compound pyruvate. The Lewis acid property of δ-MnO2 leads to a polarization of the iodine molecule, and catalyzes the reaction with natural organic matter. As manganese oxides are strong oxidants and are ubiquitous in the environment, this mechanism could significantly contribute to the global atmospheric input of iodine.